Equivalent Circuit and AC conductivity of Sr1.75Co0.25P2O7 compound (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Sr1.75Co0.25P2O7 compound was prepared by the solid-state reaction method. The impedance spectroscopy measurements were performed in the frequency and the temperature range of (209 Hz1 MHz) and (622704 K), respectively. Besides, the impedance spectra were fitted to an equivalent circuit consisting of series combination of grains and grain boundary. The AC conductivity for grain contribution is interpreted using the universal Jonschers power law. The approximation type OLPT model explains the universal behavior of the s exponent. The mechanism of conduction is probably due from the displacements of the Sr2+ ion in the tunnel-type cavities.